Investigating the moderating effect of the demographic factors on post-purchase regrets at malls in Sri Lanka - E.A.S.K. Ekanayake (Ümit Hacıoğlu, 2021)
As of 2020, the retail sector faced an existential challenge with rapid changes as one of the many sectors. The recent impact was noted due to the present COVID-19 pandemic throughout the world. Most customers have moved on with e-commerce platforms, while traditional customers still struggle with in-store shopping. This study was specifically aimed at the conventional customers who do in-store shopping in complexes. The objective of this study was to investigate the moderating effect of the demographic factors on post-purchase regret at malls. Two factors affecting post-purchase regret, namely, the number of alternatives forgone and the return process experience, were considered. Accordingly, the moderating effects of demographic factors of consumers who have purchased something from a shopping mall during the past two years were targeted for this. By conducting an online survey using a structured questionnaire, 383 responses were collected. Through the moderation effect analysis, the consumer career was identified as moderating variable for this relationship. The rest of the demographic factors considered for this study did not significantly moderate this relationship. The findings suggest that the number of alternatives in showcase must be limited with a sense of marketing. Further, the staff at the shop must provide proper guidance on the return process and related service by identifying loyal and non-loyal customers’ careers and lifestyles.